Peningkatan Kualiatas Pelayanan Menggunakan Metode Quality Function Deployment (QFD) (Studi Kasus: Perpustakaan Universitas Muhammadiyah Riau) - Dedi Dermawan; Muhammad Qurthuby; Denur Denur; Hendri Ali Ardi; Misral Misral; Japri Japri; Ayu Lestari (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The library, as an academic information center, is required to provide quality services to enhance user satisfaction. This study aims to analyze and improve the quality of library services using the Quality Function Deployment (QFD) method. A total of 99 respondents, consisting of active library users, were involved through the distribution of questionnaires. The data were analyzed using the Importance Performance Analysis (IPA) method to identify priority attributes, which were then translated into the House of Quality (HOQ) matrix. The results show that aspects such as service speed, availability of updated collections, and internet network stability are the main focuses for improvement. The proposed recommendations include enhancing the collection management system, optimizing digital services, and providing staff training to improve responsiveness and empathy toward users.